Pressureless and low-temperature sinter-joining on bare Si, SiC and GaN by a Ag flake paste. (June 2021) - Zhang, Zheng; Chen, Chuantong; Suetake, Aiji; Hsieh, Ming-Chun; Iwaki, Aya; Suganuma, Katsuaki
Abstract: In this work, we applied a Ag flake formed paste for sinter-joining on bare Si, SiC, and GaN surfaces. The sintered joints possess a high shear strength of over 40 MPa under a pressureless sintering condition at 250°C. The high bonding strength of the joints is achieved by a tight adhesion between Ag and bare surfaces, which attributed to an excellent sinter-joining ability of the Ag flake. The flakes, acquired by mechanical milling, can be rapidly sintered into a homogenous porous structure at a pleasureless and low-temperature sintering condition due to its dislocation-rich nano grain structure. During sintering, a drastic morphology reconstruction of Ag flake, from a flattened flake to a drop-like particle, can introduce robust interfacial connection structures, which is important for the robust bonding. This Ag flake paste can be regarded as a promising sinter-joining material for the connection of bare surfaces in high-temperature applications. Graphical abstract: Image, graphical abstract